1989
DOI: 10.1016/0014-5793(89)80471-5
|View full text |Cite
|
Sign up to set email alerts
|

A unique signature identifies a family of zinc‐dependent metallopeptidases

Abstract: The primary sequence motif HExxH has been found in many zinc-dependent endopeptidases. We show that a larger signature comprising this sequence is common to most of the known zinc-dependent endopeptidases, and that the presence of the signature can be indicative of membership in the family. A search of the protein sequence databases for entries containing the signature retrieved several unexpected potential zinc endopeptidases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
246
0
6

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(261 citation statements)
references
References 29 publications
9
246
0
6
Order By: Relevance
“…This histidine is within a zinc binding motif found in several metalloproteinases, but the zinc binding sequence of histatin 5 includes basic residues which are rare in non-conserved residue positions within and surrounding the consensus sequence [11]. Other histidyl C O1^H resonance changes also suggest site-speci¢c binding of zinc to histatin 5.…”
Section: Discussionmentioning
confidence: 98%
“…This histidine is within a zinc binding motif found in several metalloproteinases, but the zinc binding sequence of histatin 5 includes basic residues which are rare in non-conserved residue positions within and surrounding the consensus sequence [11]. Other histidyl C O1^H resonance changes also suggest site-speci¢c binding of zinc to histatin 5.…”
Section: Discussionmentioning
confidence: 98%
“…The region of highest identity is found at the N-terminal part of the enzyme. The encoded protein contains the signature sequence of the M1 family of zinc peptidases (HEXXH) (Jongeneel et al, 1989 ;Hooper, 1994) and this sequence was found in a region that is most conserved between ApsA, AAPI and LAPI (Fig. 1).…”
Section: Cloning Of the A Niger Apsa And Analysis Of The Genementioning
confidence: 99%
“…The majority of aminopeptidases belong to the M1 family of peptidases ; they are metalloenzymes (Van Wart, 1996) which require zinc for enzymic activity and share the zinc binding motif HEXXH (Jongeneel et al, 1989 ;Hooper, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is homology among the majority of the eight proteins at five other positions in this region. Regions of this type have been proposed as a consensus region for recognizing members of the metalloproteinase family (McKerrow, 1987;Jongeneel et al, 1989). However, fibrolase and other venom-derived metalloproteinases do not appear to share significant additional sequence homology with other, well-characterized neutral metalloendopeptidases.…”
Section: A Randolph Et Afmentioning
confidence: 99%